Ruthenoarenes versus phenol derivatives as axial linkers for subporphyrazine dimers and trimers - Caballero, Esmeralda; Nieto, Carlos Romero; Strauß, Volker; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Sessler, Jonathan L.; Torres, Tomas (Chemistry - A European Journal, 2014)
The subporphyrazine (SubPz) dimer diboron(III) [μ-1',4'-benzenediolato][bis-(1,2,6,7,11,12-hexapropylsubporphyrazinato)] (2) and trimer triboron(III)[μ-1',3',5'-benzenetriolato][tris-(1,2,6,7,11,12-hexapropylsubporphyrazinato)] (4), consisting of SubPz units assembled through their axial positions by hydroquinone- and phloroglucinol-linkers, respectively, have been prepared. Selective ruthenium-π-coordination to the linking aromatic rings afforded SubPz arrays 8 and 9, respectively. These latter systems displayed different degrees of electronic communication between the macrocycles relative to 2 and 4 as inferred from analyses of the ground- and excited-state features. For instance, as revealed by time-resolved pump probe transient absorption spectroscopy, the excited singlet states of dimer 2 and trimer 4 undergo rather rapid deactivation. In contrast, the presence of a ruthenoarene linker, as in 8 and 9, serves to increase the SubPz singlet excited state lifetimes; these now reach values similar to those seen in the case of monomeric SubPz compounds that either do or do not contain ruthenoarene subunits (i.e., 7 and 6, respectively). These findings are ascribed to the redox active nature of the hydroquinone and phloroglucinol linkers in 2 and 4 and a change in the electronics that results from organometallic functionalization. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.